Linguistic equivalence of the name Sheol/sheol in Polish translations of the Bible - Zarębski, Rafał (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The author study different equivalents of the Hebrew word Sheol in selected old and new Polish translations of the Bible. The equivalents of this lexeme have been excerpted from different translations of the Bible, which were selected on the basis of diverse criteria. The translations are presented chronologically and old translations are opposed to the new ones. They are connected with the base of translations, i.e. the original text and/or Greek or Latin text. They can also be classified according to religious denomination and the strategy of the translation. The observation of those equivalents enables us to see not only their variety and mutual influence among translations but also the struggle of translators with a very difficult language matter. Many factors were important in that struggle: genetic and structural distances between Semitic languages and Polish, different perceptions of reality in distant cultures, the discrepancy between biblical and Slavonic realities and the influence of religious denomination. Another important factor was the state of biblical knowledge at the time — incomparably poorer in the case of the oldest Polish translations in comparison to modern ones.